2017
DOI: 10.1515/epoly-2016-0329
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight sponges of poly(para-xylylene) by template-assisted chemical vapour deposition

Abstract: Abstract:Particle foams and open cell sponges play nowadays an important role in academia and industrial research. The fabrication of new high-performance foams is one of the challenges. Until now, it is impossible to visualise the quality of particle foams, and the quantification is only possible with expensive analytical methods like scanning electron microscopy. In this work, we demonstrate a simple method for the visualisation of void sizes and defects inside particle foams on the basis of expanded polysty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Different kinds of degradable polymers can be used for scaffold production, e.g. polylactide (PLA), ,, poly­(lactide- co -glycolide) (PLGA), PLGA/Collagen, PLA/PHBV, poly­(ε-caprolactone) (PCL), , chitosan, PLA/chitosan, and cellulose systems. , By comparison, only a modest number of 3D scaffold fabrication techniques have been developed that provide a dynamic framework with high porosity, a broad user-adjustable structural and mechanical integrity in combination with chemical diversity . Moreover, in order to work as an artificial ECM, the scaffold has to bridge the gap between mechanical and biochemical requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of degradable polymers can be used for scaffold production, e.g. polylactide (PLA), ,, poly­(lactide- co -glycolide) (PLGA), PLGA/Collagen, PLA/PHBV, poly­(ε-caprolactone) (PCL), , chitosan, PLA/chitosan, and cellulose systems. , By comparison, only a modest number of 3D scaffold fabrication techniques have been developed that provide a dynamic framework with high porosity, a broad user-adjustable structural and mechanical integrity in combination with chemical diversity . Moreover, in order to work as an artificial ECM, the scaffold has to bridge the gap between mechanical and biochemical requirements.…”
Section: Introductionmentioning
confidence: 99%
“…[ 69 ] In a report by Greiner and co‐workers, they made 3D foam structures using a template‐assisted approach, wherein expanded polystyrene and sugar cubes were used as template foams. [ 70 ] PPX polymer was then coated on these foams, and subsequently, the template foam structure was dissolved to obtain inverse foam structures. In this particular case, inverse foam structures made up of parylene polymers gave insight into the actual foam structure and properties and, at the same time, showed interesting wetting behavior and thermal properties that can be exploited for use in various applications.…”
Section: D To 3d Spatial Architectures By Templated Cvd Polymerizationmentioning
confidence: 99%
“…Recently, we observed that porous materials such as sugar cubes can act as templates for the generation of ultralight PPX foams. [ 41 ] These foams exhibit interesting properties such as good thermal insulation or the ability to separate oil/water mixtures. Although complex structures can be coated, it is known that the thickness of coatings through small holes decreases with increasing distance ( Figure ).…”
Section: Background Of Ppxmentioning
confidence: 99%